Older patients’ experiences of nurse-to-nurse collaboration between hospital and primary health care in the care chain for older people - Terhi Lemetti; Päivi Voutilainen; Minna Stolt; Sini Eloranta; Riitta Suhonen (Blackwell Science, 2022)
Background: Nurse‐to‐nurse collaboration between nurses working in hospital and primary health care in the older people care chain is essential to ensure the continuity of care. The nature of good collaboration in this context is understood usually from the perspective of collaborating nurses. However, there seems to be a lack of research about this collaboration from the older patient's perspective who are at the centre of the collaboration.
Aims and objectives: To describe older patient's experiences of the collaboration between hospital and primary healthcare nurses delivering care to older people.
Design: A qualitative approach based on a descriptive phenomenological methodology was used.
Methods: Individual interviews were conducted using a purposeful sample of older patients (n = 18) who were cared for both in hospital and primary healthcare organisations. A qualitative data analysis method informed by Giorgi was used.
Results: The essence of the experience of nurse‐to‐nurse collaboration between hospital and primary health care was expressed as follows: the meaning of collaboration; the elements of collaboration valued; the visibility of collaboration; older patient involvement in collaboration; interaction within collaboration; and future expectations of collaboration.
Conclusions: Although nurse‐to‐nurse collaboration between hospital and primary health care was not often visible to older patients, they highlighted the importance of this collaboration to ensure the continuity of care. The participants would have liked to be part of the collaborating group, at the centre of care, cared for by motivated nurses who had a clear understanding of their patients’ health status. This study emphasises the need for improving collaboration between hospital and primary healthcare nurses by making it more visible and facilitating older patients’ participation. The results demonstrate the need to understand patient perspectives in the development of care and the services provided for older people.